Appendix 1.3: Letter from the Office of the Chancellor to UP President Alfredo Pascual on the Request to Rename the College of Business Administration into the Cesar E.A. Virata School of Business, 11 April 2013 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Chancellor Caesar Saloma wanted guidelines for renaming constituent institutions (not structures) of the University of the Philippines to be formulated before the College of Business Administration could become the Cesar E.A. Virata School of Business. However, it appears that he was also the first to highlight the distinction between renaming a unit/entity and renaming a concrete structure, which later became a defense of those who supported the renaming. There are still no guidelines in the University of the Philippines for renaming constituent institutions as of this writing.